Compact waves on planar elastic rods - Durickovic, B; Goriely, A; Saccomandi, G (2009)
Planar Kirchhoff elastic rods with non-linear constitutive relations are shown to admit traveling wave solutions with compact support. The existence of planar compact waves is a general property of all non-linearly elastic intrinsically straight rods, while intrinsically curved rods do not exhibit this type of behavior. © 2008 Elsevier Ltd. All rights reserved.